Metode Pembelajaran “Permainan 3 On 3” Untuk Meningkatkan Kemampuan Passing Bawah Bola Voli Pada Siswa - Purwanto, Hadi (STAMINA, 2023)
This study aims to analyze the 3 On 3 Game Learning method to improve Volleyball Bottom Passing ability in Students. This research uses a qualitative approach. The type of research carried out is classroom action research (PTK) by improving each learning cycle. The research sample was students of grade VIII-H SMP Negeri 10 Jember with a total of 34 students. The instrument used is an observation sheet of learning process skills observed by the teacher which is then analyzed by looking for the percentage score of each aspect of the skill Based on the results of the study, it was concluded that the 3 on 3 game can improve the process and passing ability under volleyball in grade VIII H students of SMP Negeri 10 Jember. This can be seen from the learning process and student learning outcomes which always increase from cycle 1 to cycle II and the percentage result of cycle II is 82.96%. Teaching using 3 on 3 games can make volleyball bottom passing learning in grade VIII-H students of SMP Negeri 10 Jember better, students are more enthusiastic and feel happy in following the learning carried out and look not bored.